PEMODELAN KOLIMATOR DI RADIAL BEAM PORT REAKTOR KARTINI UNTUK BORON NEUTRON CAPTURE THERAPY - Vallenry, Bemby Yulio; Widiharto, Andang; Sardjono, Yohannes (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
One of the cancer therapy methods is BNCT (Boron Neutron Capture Therapy). BNCT utilizes neutron nature by 10B deposited on cancer cells. The superiority of BNCT compared to the rradiation therapy is the high level of selectivity since its level is within cell. This study was carried out on collimator modelling in radial beam port of reactor Kartini for BNCT. The modelling was conducted by simulation using software of Monte CarloN-Particle version5 (MCNP 5). MCNP5 is a package of the programs for both simulating and calculating the problem of particle transport by following the life cycle of a neutron since its birth from fission reaction, transport on materials, until eventually lost due to the absorption reaction or out from the system. The collimator modelling used materials which varied in size in order to generate the value of each of the parameters in accordance with the recommendation of the IAEA, the epithermal neutron flux (Фepi) > 1.0 x 109n.cm-2s-1, the ratio between the neutron dose rate fast and epithermal neutron flux (Ḋf/Фepi) < 2.0 x10-13 Gy.cm2.n-1, the ratio of gamma dose rate and epithermal neutron flux (Ḋγ/Фepi) < 2.0 x10-13 Gy.cm2.n-1, the ratio between the thermal and epithermal neutron flux (Фth/Фepi) < 0.05 and the ratio between the current and flux of the epithermal neutron (J/Фepi) > 0.7. Based on the results of the optimization of the modeling, the materials and sizes of the collimator construction obtained were 0.75 cm Ni as collimator wall, 22 cm Al as a moderator and 4.5 cm Bi as a gamma shield. The outputs of the radiation beam generated from collimator modeling of the radial beam port were Фepi = 5.25 x 106 n.cm-2.s-1, Ḋf/Фepi = 1.17 x 10-13 Gy.cm2.n-1, Ḋγ/Фepi = 1.70 x 10-12 Gy.cm2.n-1, Фth/Фepi = 1.51 and J/Фepi = 0.731. Based on this study, the results of the beam radiation coming out of the radial beam port did not fully meet the criteria recommended by the IAEA so need to continue this study to get the criteria of IAEA.